Narrowing the Gap Between LIS Research and Practice in Australia. Issue 1 (2nd January 2018) - Nguyen, Linh Cuong; Hider, Philip
Abstract: Concerns about the gap between LIS theory and practice have been voiced by many commentators over the years. A moderate gap was identified between the research priorities of practitioners in the Relevance 2020 project's focus groups, convened across Australia in late 2016, and the LIS research actually being conducted. A total of 172 Relevance 2020 participants, from a wide range of sectors, identified 96 priority topics, in areas such as the role of libraries and librarians, promotion, information service operations and information literacy. The participants also suggested ways in which LIS research could be better supported and made more relevant to practice. All stakeholders need to play their complementary parts: employers need to support practitioners' involvement in research, as well as their engagement with it; professional networks can help lobby for funds and resources, and facilitate the development of research capacity; academics can identify areas in which their own agendas coincide with those of practitioners, and explain the relevance of their research findings. Strong partnerships between individual practitioners and researchers can be formed by first identifying common ground and aims, through the sort of constructive dialogue generated at the Relevance 2020 events.